Hukuman Bagi Pelaku Tindak Pidana Membawa Lari Anak Perempuan - Mustakhim, Mustakhim (Al-Jinayah: Jurnal Hukum Pidana Islam, 2015)
Abstract: This study discusses the decision No. 09/Pid.B/2012/ PN.Mojokerto about criminal act of carrying off an under age woman without permission of her parents. In the judgeâs ruling, it is declared that the defendant has been proven legally and convincingly guilty of committing a criminal offense by carrying off an under age woman without permission of her parents, but only with the consent of the woman outside of marriage. The offense complain is imprisonment for 1 (one) year and 2 (two) months because the defendant violated Article 332 Paragraph (1) of the Criminal Code. In addition, the defendant is also burdened to pay court fees. In the study of Islamic criminal law, punishment for carrying off an under age woman is taâzÃ®r jarÃ®mah (criminal penalty). These penalties vary and can be determined by ulil amri or government official or judge who is given authority to enforce with some considerations and other reasons in accordance with Islamic criminal law.Keywords: Penalty, carrying off, daughter.Â Abstrak: Artikel ini membahas tentang putusan perkara Nomor 09/Pid.B/2012/PN.Mojokerto tentang tindak pidana membawa lari seorang perempuan yang belum dewasa tanpa izin orang tuanya. Dalam putusan hakim tersebut, dinyatakan bahwa terdakwa telah terbukti secara sah dan meyakinkan bersalah melakukan tindak pidana membawa lari seorang perempuan yang belum dewasa tanpa izin orang tuanya tetapi dengan persetujuan perempuan itu di luar perkawinan. Delik aduannya adalahÂ  pidana penjaraÂ  selamaÂ  1 (satu) tahun 2 (dua)Â  bulan karena perbuatan terdakwa melanggar Pasal 332 Ayat (1) KUHP. Selain itu, terdakwa juga dibebani membayar biaya perkara. Dalam kajian hukum pidana Islam, hukuman membawa lari seorang perempuan yang belum dewasa merupakan hukuman jarÄ«mah taâzÃ®r. Hukuman ini berbeda-beda, dan dapat ditentukan hukumannya oleh ulil amri atau aparat pemerintah yang diberikan wewenang untuk menyelenggarakan hukuman tersebut di mana hukumannya ringan dan beratnya dapat ditentukan oleh hakim Pengadilan Negeri Mojokerto dengan beberapa pertimbangan dan alasan-alasan lainnya sesuai dengan hukum fiqh jinÃ¢yah.Kata Kunci: Hukuman, membawa lari, anak perempuan.